Butterworth band-pass filter using parallel coupled lines for WiMAX application: article / Siti Azidah Abidin, Kamariah Ismail and Suhana Sulaiman - Abidin, Siti Azidah (2009)
This paper describes the design, simulation and analysis of a Butterworth band-pass filter using parallel coupled line for WiMAX application. Butterworth approach was used in designing the filter and the simulation was carried out using Genesys simulation software. The performance of the filter was simulated based on Rogers Duroid 4350B with dielectric substrate (Єr) is 3.48. The operating frequency range from 5.7175GHz to 5.8225GHz with the cut-off frequency 5.770 GHz with the consideration of 100MHz bandwidth. It was observed that both the simulated and measured values were close.